PENGEMBANGAN MEDIA DIGITAL FLASH CARD BERBASIS BUDAYA SAGELE UNTUK MENINGKATKAN PEMAHAMAN KONSEP PEMBELAJARAN IPAS SISWA SEKOLAH DASA - Ija Srirahmawati; Putri Surya Damayanti; Desy Cahya Ramdani; Nabila Sagita Ramdhan (Al-Aulad: Journal of Islamic Primary Education, 2025)
Learning Science, Social Studies, and Arts (IPAS) in elementary schools is often constrained by the lack of interactive local culture-based media, leading to low student comprehension. This research aims to develop digital flash card media based on the distinctive Sagele culture of Dompu to enhance IPAS concept comprehension. The Research and Development (R&D) method, specifically the 4-D model (Define, Design, Develop, and Disseminate), was employed at SDN 3 Pajo, with 24 fifth-grade students as the sample. Instruments included validation sheets, response questionnaires, and concept comprehension tests (pre-test/post-test). The results indicate that this media is Highly Valid (93.0%) according to experts, Highly Practical (88.0%) based on teacher and student responses, and Effective in improving IPAS concept comprehension. A significant increase was observed in the average post-test score (82.50) compared to the pre-test (48.33), with an N-gain of 0.66 (Moderate category). The integration of Sagele culture proved crucial in creating a contextual and meaningful learning experience for students. In conclusion, the digital flash card media based on Sagele culture is a successful learning innovation, effectively improving IPAS concept comprehension while simultaneously promoting local wisdom. This product holds significant potential for broader adoption to support relevant and contextual learning in the future